2021
DOI: 10.1016/j.envres.2021.110972
|View full text |Cite
|
Sign up to set email alerts
|

Is coronavirus disease (COVID-19) seasonal? A critical analysis of empirical and epidemiological studies at global and local scales

Abstract: Coronavirus disease (COVID-19) has infected more than 50 million people and killed more than one million, worldwide, during less than a year course. COVID-19, which has already become the worst pandemic in the last 100 years, is still spreading worldwide. Since the beginning of the outbreak, it has been of particular interest to understand whether COVID-19 is seasonal; the finding might help for better planning and preparation for the fight against the disease. Over the past 12 months, numerous empirical and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
63
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 121 publications
8
63
0
1
Order By: Relevance
“…The results of our systematic review are in agreement with three previous reviews [ 12 , 13 , 14 ], suggesting a negative correlation between ambient temperature and humidity and the number of COVID-19 cases, but these previous reviews also report heterogenous findings, with some studies reporting no or even a positive correlation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of our systematic review are in agreement with three previous reviews [ 12 , 13 , 14 ], suggesting a negative correlation between ambient temperature and humidity and the number of COVID-19 cases, but these previous reviews also report heterogenous findings, with some studies reporting no or even a positive correlation.…”
Section: Discussionsupporting
confidence: 92%
“…In light of the above observations, it can be surmised that there may also be a dependence of SARS-CoV-2 transmission on weather variables. There have been reviews published regarding the association between weather variables and SARS-CoV-2 transmission [ 12 , 13 , 14 ]. Yet, these reviews showed contradicting results and they did not assess the quality of the included studies, which would put more weight on the conclusions of studies having a lower risk of bias.…”
Section: Introductionmentioning
confidence: 99%
“…variants of interest, monitored for potential implications regarding the pandemic, and especially, variants of concern (VOC), confirmed to have serious implications in individual countries. 9 13 Furthermore, the level of vaccination within the population has become the biggest driver of decreasing IFR as, despite varying degrees of protection against symptomatic and asymptomatic disease, the level of protection against death is particularly high and reaches close to 100%. The reasons include not only lowering the IFR in the small fraction of breakthrough infections within the most vulnerable age groups but also the prevention of healthcare system overload, maintaining high quality healthcare accessible to all those in need.…”
Section: Epidemiologymentioning
confidence: 99%
“…As of June 18, 2021, the World Health Organization (WHO) has reported a cumulative total number of 177,108,695 confirmed cases of coronavirus disease (COVID- 19) worldwide. SARS-CoV-2 is an emerging human coronavirus with many similarities to common HCoVs [12]. SARS-CoV-2 infection may cause severe illness; however, a substantial proportion of SARS-CoV-2 infections are mild and asymptomatic, with approximately 40% of infections being completely asymptomatic and some infections are not diagnosed due to the limited severity of the symptoms [13].…”
Section: Introductionmentioning
confidence: 99%